Controllable synthesis of self-templated hierarchical Ni3S2@N-doped carbon for enhanced oxygen evolution reaction. Issue 12 (17th May 2021) - Wang, Shuai; Lu, Zheng; Fang, Yuan; Zheng, Tian; Zhang, Zidong; Wang, Wenjian; Zhao, Rui; Xue, Weidong
Abstract : The self-supporting electrode exhibits enhanced electrocatalytic activity and stability due to 3D structure, modified electronic structure, and rapid charge transfer capability, which opens up a promising avenue for highly efficient OER. Abstract : Rational construction of self-supporting electrodes has been extensively investigated in energy conversion and storage. In this work, hierarchical N-doped carbon-encapsulated Ni3 S2 grown on a 3D porous Ni foam (H-Ni3 S2 @NC/NF) was controllably synthesized by a one-pot self-templated solvothermal method. Herein, we highlight the self-templated growth of multilayered Ni3 S2 with N-doped carbon intercalation at a certain temperature. The unique H-Ni3 S2 @NC/NF shows enhanced active sites and a modulated electronic structure, which facilitates mass/electron transport. Thereby, the H-Ni3 S2 @NC outperforms a lower overpotential of 238 mV at 10 mA cm −2 and a low Tafel slope of 62 mV dec −1 than that of binary and ternary metal sulfides, suggesting an excellent mono-metal sulfide as a self-supporting electrode for oxygen evolution reaction.